Phylogeny in Echinocereus (Cactaceae) based on combined morphological and molecular evidence: taxonomic implications. Issue 1 (2nd January 2018) - Sánchez, Daniel; Terrazas, Teresa; Grego-Valencia, Dalia; Arias, Salvador
Abstract : Echinocereus is a morphologically diverse genus that includes 64 species grouped into eight taxonomic sections based on morphological traits. In previous molecular phylogenetic analyses, the relationships amongst Echinocereus species were not entirely revealed and useful characters to recognize clades were not provided. The inclusion of several sources of evidence in a phylogenetic analysis is likely to produce more supported hypotheses. Therefore, we performed a combined phylogenetic analysis with a set of 44 morphological characters and six chloroplast DNA sequences. Topologies from parsimony and Bayesian analyses were mostly congruent. However, the relationships of E. poselgeri were not consistent between analyses. A second Bayesian analysis using a long-branch extraction test resulted in a topology with the morphological position of E. poselgeri congruent with that in parsimony analysis. Parsimony and Bayesian analyses corroborated the monophyly of Echinocereus, which included eight monophyletic groups. The combined phylogeny integrated into different clades those taxa that were not determined in previous analyses and changed the relationships of some recognized clades. The clades did not recover the recent infrageneric classification. In the present study, a new sectional classification for Echinocereus is proposed based on the eight recovered clades, which is supported by a combination of morphological and molecular characters. An identification key for sections in the genus is included.